Back Flow-Injection Spectrophotometric Determination of Selected Fluoroquinolones - A. Barakat, Salem (Current Analytical Chemistry, 2017)
Flow Injection analysis is mainly applied to automate or semiautomatic determination of some analytes. This is called flow injection analysis. However some reactions are slow and can’t be analysed via direct flow injection analysis. The aim of this work is to develop a method suits slow reactions. The method is based on the reaction of quinolones with excess Iron(III) nitrates. Excess amount of iron(III) added to quinolone forms an amber color. The excess iron is determined after complexing it using potassium thiocyanate in acidic medium to form red complex with higher absorptivity coefficient, which is then spectrophotometrically determined at 525nm. This technique may be called back flowinjection technique, as it is called in back titration technique with a slight modification. A modified Flow-injection spectrophotometric method (FIA) of analysis has been developed for the separate determination of ofloxacin, norfloxacin and ciprofloxacin antibiotics. The method is applied to the determination of quinolones in commercial tabulated forms available in the market. The manifold is designed so that constant flow rate of Iron(III), quinolone and sulfuric acid mixed and the baseline of the complex is set. Fixed amount of thiocyanate is then injected and the absorbance of the red colored complex formed between excess Iron(III) and thiocyanate is recorded. Lambert-Beers low was maintained in the range 0.1-90 ppm. The recovery was better than 99%. The detection limit reaches 20μg/l. The FIA method is fast (20/h), sensitive, precise, cheap to run and gave reasonable results. The method is suitable for slow rate reactions between analyte and complexing agents, which cannot be determined by direct flow-injection analysis.
Keywords: ofloxacin